Improving order-to-delivery process : Case study:Company X - Lehtinen, Alisa (My University, 2020)
Improving companies’ processes is one of the core ways to gain competitive advantage in today’s markets. Identifying the problem areas and finding solutions for them is an essential part of companies’ survival and therefore companies are investing in process improvement even more especially when they are preparing themselves for changes. Improving the company’s operations in engineer-to-order environments differs from the other manufacturing strategies due to the lack of standardization in the order-to-delivery process. The purpose of this research is to discover the issues that engineer-to-order manufacturing companies are struggling with and to find ways to improve the case company’s order-to-delivery process. This research also considers the ways that the process and its practices can be standardized in the engineer-to-order environment. The aim is to provide information of the company’s current process and its problems and find solutions for those issues to improve the overall performance of their order-to-delivery process. At the beginning of this research there is a literature review which contains the basic phases of process improvement, the stages and characteristics of the order-to-delivery process in engineer-to-order environment and the common methodologies for process improvement. The information from the literature review is used to form common themes for the empirical part of the research. The empirical part is a single case study where the data is collected through a workshop, interviews and observations. The data is analyzed with fishbone diagrams, five whys tool and with a value stream map. The results from the analysis are used to evaluate the company’s process and to create solutions for the company to implement afterwards. Based on the results, many of the problems in the engineer-to-order environment can be derived from the lack of standardization in the process and its practices. Bad communication practices are creating several other problems and creating better, more standard, ways to communicate and document all actions and data in daily bases is critical for the company’s process performance to be improved. Many phases, as well as the products, can be standardized in some way, but making those changes requires time and resources that must be saved and relocated from the on-value adding activities that are currently done. Measuring the process provides valuable information about the performance and helps identifying problem areas. Managements participation and employees’ proactive attitudes are incredibly important for the process to be successfully improved. This is a single case study for a small company in a very specific business field, and therefore the generalization of the results can be questioned. The results are used to improve the case company’s performance but other SME companies working in engineer-to-order environment can use the results as guidance in their own process improvement projects.
Keywords: business; processes; improving; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management